Accessibility in the hotel industry of the State of Rio de Janeiro, Brazil (Research, Society and Development, 2020)
This paper aims to analyze the hotel industry accessibility issue in 5 touristic regions of the State of Rio de Janeiro - Sun Coast, Coffee Valley, Green Coast, Black Needles and Imperial Green Mountain. The key point of the study was to diagnose how hotel buildings were prepared to receive tourists with special needs. The methodology used a statistical modeling to analyze the data obtained through the Inventory of the Tourist Offer of the State of Rio de Janeiro (IOT-RJ), carried out between 2015 and 2017, in 21 cities that belongs to these regions, including 1.834 hotel units. The relevance of the study is to contribute to the awareness of the civil construction and tourist trades in relation to people with disabilities or reduced mobility needs. As a conclusion, it is highlighted that investigated hotels in these regions do not have the minimum accessibility requirements to promote a great experience for special needs individuals (SNI).